Effect Size of Fillers on Discoloration of dental composite - عبدلله, عاطف (Latakia University Journal -Medical Sciences Series, 2021)
Objective: The purpose of this study was to investigate the effect of size of Composite fillers on Discoloration in order to investigate the best kind of these materials in clinical performance. Materials and Methods: Two composite materials were used that were Tetric N Ceram and Tetric Evo Ceram of Ivoclar Vivadent company. Forty conventional class І filling were prepared in dimensions (2x2x2) mm on the occlusal surface of first and second permanent molars of (20) patients and were observed for (one month, 6 months) to investigate discoloration. Results: Discoloration with Tetric N Ceram group was more than Tetric Evo Ceram group in observation periods.